Interdisciplinarity and Language - Coseriu, Eugeniu (Acta Universitatis Danubius. Communicatio, 2022)
In this text published in 1980 (but based on a conference talk from 1978), still valid in its content, Eugenio Coseriu makes a series of essential distinctions within the concept of ‘interdisciplinarity’. At the same time, the respective distinctions are useful to the Romanian scholar in order to establish the place of linguistics (and, most of all, of his ‘integral linguistics’) among cultural sciences, in accordance with the reality of language and its aspects or manifestations. Consequently, since language does not only consist in structures, one can notice that Coseriu’s integral linguistics goes beyond structuralism. The latter part of this translation consists of Coseriu’s replies and interventions during the discussions that followed the delivery of his paper.